2000
DOI: 10.1557/jmr.2000.0400
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum diffusion barrier grown by inorganic plasma-promoted chemical vapor deposition: Performance in copper metallization

Abstract: As-deposited and annealed tantalum films, grown by plasma-promoted chemical vapor deposition (PPCVD) using pentabromotantalum and hydrogen as coreactants, were evaluated as diffusion barriers in copper metallization. Stacks consisting of 500-nm-thick sputtered Cu/55-nm-thick untreated PPCVD Ta/Si were annealed in argon in the range 450 to 650 °C, in 50 °C intervals, along with sputtered Cu/preannealed PPCVD Ta/Si and sputtered Cu/sputtered Ta/Si stacks of identical thickness. Pre- and postannealed stacks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Thus, halide precursors are the only commercially available metal precursors for Ta CVD currently. While Ta CVD using chloride requires rather high growth temperature, Ta films were deposited at 450 °C using plasma-enhanced CVD with TaBr 5 and hydrogen plasma, (149,150) The only reported Ta ALD was a plasma enhanced process. (27,43) When TaCl 5 was used as metal precursor and atomic hydrogen produced by RF plasma as reducing agent, amorphous Ta thin films have been deposited at temperatures below 250 °C.…”
Section: Tantalum and Tantalum Nitirdesmentioning
confidence: 99%
“…Thus, halide precursors are the only commercially available metal precursors for Ta CVD currently. While Ta CVD using chloride requires rather high growth temperature, Ta films were deposited at 450 °C using plasma-enhanced CVD with TaBr 5 and hydrogen plasma, (149,150) The only reported Ta ALD was a plasma enhanced process. (27,43) When TaCl 5 was used as metal precursor and atomic hydrogen produced by RF plasma as reducing agent, amorphous Ta thin films have been deposited at temperatures below 250 °C.…”
Section: Tantalum and Tantalum Nitirdesmentioning
confidence: 99%
“…2,7,9,11,[111][112][113][114][115] These volatile and relatively easy to handle precursors have dominated the field of diffusion barrier film deposition for nearly three decades. 114,[117][118][119][120] Hafnium alkylamides (for example, tetrakis-(dimethylamido)-hafnium, Hf[N(CH 3 ) 2 ] 4 ) have a set of remarkable properties as precursors for growth of a variety of Hfcontaining films, 34,115,[121][122][123][124][125][126][127] including hafnium dioxide, a high-k dielectric material with a wide range of current and potential applications. 12,[47][48][49][50]116 Contamination has been reduced with the use of ALD schemes (with water or ammonia as secondary precursors for the respective growth of oxides and nitrides); various post-treatment methods have also led to dramatic improvements of the deposited films.…”
Section: B Surface Reactions Of Hf[n(ch 3 ) 2 ] 4 As An Example Of Mmentioning
confidence: 99%
“…Chemical vapor deposition (CVD) offers promising solutions to the problems associated with IM-CMS coatings. Reported studies have demonstrated the use of CVD in producing Ta coatings from tantalum halide sources [1][2][3][4][5]. High quality CVD Ta coatings were produced with excellent step coverage in sub-micron trench structures with high aspect ratios as shown below in Figure 1…”
Section: Background 21 Problem Addressed By This Technologymentioning
confidence: 99%